PENDAMPINGAN MASYARAKAT KABUPATEN BENER MERIAH MELALUI PEMANFAATAN LIMBAH KULIT KOPI SEBAGAI ENERGI BARU TERBARUKAN - Yulian, Muammar (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Energy is one of the primary needs in supporting various activities. Most of the energy we use comes from fossil energy. Therefore fossil energy source was known to be limited and not environmentally friendly, so an alternative energy source or known as renewable energy is needed, such as bioethanol. Coffee pulpas raw material is a by-product from the coffee processing industry that can be used for bioethanol production. Through community engagement, it is hoped that the community can utilize and process coffee skin waste more optimally, from previously only composting to something that has added value, such as bioethanol. The community engagement took place on Mupakat Jadi Village, Bukit District, one of the main coffee-producing villages in Bener Meriah Regency. The process of processing coffee skin waste into bioethanol is carried out by involving the active participation of the community and carried out by laboratory procedures that have been modified in such a way that they are simple and easy to apply by the general public. This process begins with collecting coffee skin waste, then drying and grinding the skin waste, next that it is fermentation using vinegar and yeast, the fermentation process lasts for 24 hours so that ethanol was forming.